“Human rights” in the protection of rural women’s land rights and interests in China, 2000–2022: judicial perspective - Zhang, Yonghe; Huang, Xiaoyi (Humanities & social sciences communications, 2024)
In mainland China, rural women still suffer from unequal treatment in the distribution of land rights and interests. On the conceptual level, the distribution of land rights in China’s rural areas is often characterized by gender-based discrimination. On the institutional level, although Chinese law clearly stipulates that “women and men enjoy equal rights”, it makes no corresponding provision for issues concerning the land rights and interests of women who have changed their place of residence due to marriage. In the case of a conflict between law and custom, justice is the ultimate means to resolve the conflict. According to civil judicial judgment documents (CJJDs) in China Judgment Online, the term “human rights” frequently appears in cases of rural women’s land rights and interests (RWLRIs), which has positive effects on the judicial protection of RWLRIs. “Human rights” shows a relatively concentrated trend in time-based distribution and geographical distribution, respectively. Moreover, “human rights” appears both in the claims of litigants and in the reason of judgment decision-making of judges. The use of “human rights” by judges in their reasons for judgment decision-making reflects the role of “human rights” in interpreting ambiguous rules in judicial activities. Additionally, the use of “human rights” in CJJDs involving RWLRIs reflects at least three human rights concepts. Although using the term “human rights” provides a “program” for protecting RWLRIs in mainland China, it is not enough to rely solely on judges to use “human rights” to protect women’s rights. Only by clarifying the legal norms can we effectively help rural Chinese women get out of their plight.